2021
DOI: 10.1186/s12951-021-00781-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of EphA2 siRNA-loaded lipid nanoparticles and combination with a small‐molecule histone demethylase inhibitor in prostate cancer cells and tumor spheroids

Abstract: Background siRNAs hold a great potential for cancer therapy, however, poor stability in body fluids and low cellular uptake limit their use in the clinic. To enhance the bioavailability of siRNAs in tumors, novel, safe, and effective carriers are needed. Results Here, we developed cationic solid lipid nanoparticles (cSLNs) to carry siRNAs targeting EphA2 receptor tyrosine kinase (siEphA2), which is overexpressed in many solid tumors including prost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…EphA2, which activates downstream signaling pathways in combination with its ligand EphrinA1, plays a crucial role in cell proliferation and cell transformation [10]. Recently, EphA2 has been found to be expressed at high level in tumor tissues and its overexpression is closely associated with the development of tumor cells [11][12][13]. Increasing evidence indicated that EphA2 may be a potential regulatory factor in the progression of HCC and EphA2 overexpression can lead to tumor angiogenesis, lymph node metastasis and satellite tumor lesions in HCC tissues [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…EphA2, which activates downstream signaling pathways in combination with its ligand EphrinA1, plays a crucial role in cell proliferation and cell transformation [10]. Recently, EphA2 has been found to be expressed at high level in tumor tissues and its overexpression is closely associated with the development of tumor cells [11][12][13]. Increasing evidence indicated that EphA2 may be a potential regulatory factor in the progression of HCC and EphA2 overexpression can lead to tumor angiogenesis, lymph node metastasis and satellite tumor lesions in HCC tissues [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The linear PEI–siRNA conjugate was nonimmunogenic and cytocompatible. Also, PEGylated PEI/siRNA can be advanced using a copolymer/mixed polymer that is extra stable and its hydrophilic layer formed by PEG polymer coating outside the PEI/siRNA conjugate reduces NCs aggregation. , Similarly, instead of 1,2-di- O -octadecenyl-3-trimethylammonium propane (DOTMA), dimethyldioctadecylammonium bromide (DDAB) cationic lipid NCs are used to transfect siRNA, resulting in increased cellular uptake and excellent silencing properties when compared to commercially available transfection reagents (Dharmafect 2) . For example, polyamidoamine dendrimer NCs modified with methyl ether PEG and poly- l -lysine (PLL) improve tumor penetrability when paired with Polo-Like Kinase (PLK-1) siRNA.…”
Section: Advantages Of Nanocarriers (Ncs) For Sirna Deliverymentioning
confidence: 99%
“…It regulates cell proliferation, survival and differentiation; moreover, it is overexpressed in many cancers including PC [100]. Oner et al [88] employed cationic solid lipid nanoparticles (cSLNs) to deliver siRNAs targeting EphA2 (siEphA2). In PC3, DU145 (non-androgenresponsive PC cells) it was shown that cSLNs loaded with a fluorescent siRNA could transfect about 80% of the cells, turning out to be superior to a commercial transfection reagent.…”
Section: Sirna Delivery In Pc 321 Lipid-based Delivery Approachesmentioning
confidence: 99%